Preventing Candida albicans from subverting host plasminogen for invasive infection treatment - Si-Min Chen; Zui Zou; Shi-Yu Guo; Wei-Tong Hou; Xi-Ran Qiu; Yu Zhang; Li-Jun Song; Xin-Yu Hu; Yuan-Ying Jiang; Hui Shen; Mao-Mao An (Emerging Microbes and Infections)
Candida albicans is a common fungal pathogen in humans that colonizes the skin and mucosal surfaces of the majority healthy individuals. How C. albicans disseminates into the bloodstream and causes life-threatening systemic infections in immunocompromised patients remains unclear. Plasminogen system activation can degrade a variety of structural proteins in vivo and is involved in several homeostatic processes. Here, for the first time, we characterized that C. albicans could capture and “subvert” host plasminogen to invade host epithelial cell surface barriers through cell-wall localized Eno1 protein. We found that the “subverted” plasminogen system plays an important role in development of invasive infection caused by C. albicans in mice. Base on this finding, we discovered a mouse monoclonal antibody (mAb) 12D9 targeting C. albicans Eno1, with high affinity to the 254FYKDGKYDL262 motif in α-helices 6, β-sheet 6 (H6S6) loop and direct blocking activity for C. albicans capture host plasminogen. mAb 12D9 could prevent C. albicans from invading human epithelial and endothelial cells, and displayed antifungal activity and synergistic effect with anidulafungin or fluconazole in proof-of-concept in vivo studies, suggesting that blocking the function of cell surface Eno1 was effective for controlling invasive infection caused by Candida spp. In summary, our study provides the evidence of C. albicans invading host by “subverting” plasminogen system, suggesting a potential novel treatment strategy for invasive fungal infections.